Spatiotemporal characteristics and influencing factors of renewable energy production in China: A spatial econometric analysis - Xu, Jie; Lv, Tao; Hou, Xiaoran; Deng, Xu; Li, Na; Liu, Feng (Energy economics, 2022)
This study investigates the spatiotemporal distribution characteristics and influencing factors of renewable energy production to inform the optimization of renewable energy production distribution. A spatial analysis of specific mechanisms of China's renewable energy production is required. Using panel data of 30 Chinese provinces from 2001 to 2020, we employed the spatial Gini coefficient and standard deviation ellipse method to investigate the degree of spatial agglomeration and characteristics of distribution of location of China's renewable energy production. Then, we explored spatiotemporal regularity, spatial correlation, and spillover effects of renewable energy production by applying Moran's I index and the spatial Durbin model (SDM). Results show that China's renewable energy production presents prominent spatial agglomeration characteristics, and the spatial agglomeration of solar power is significantly higher than those of other renewable energies. There is a significant positive spatial autocorrelation in China's renewable energy production. Provinces with high (low) development levels in terms of renewable energy production are surrounded by provinces with high (low) development levels. Results of the SDM indicate that China's renewable energy production has an apparent spillover effect affecting neighboring areas. Transmission infrastructure, environmental regulation, and urbanization level can significantly promote the renewable energy production. Gross domestic product per capita, energy intensity, SO2 emissions, and urban population have significant negative inhibitory effects, while foreign direct investment, research and development investment, and carbon dioxide emissions have insignificant effects. The results of this study will be of great significance for policy-makers and scholars to accurately identify the spatial spillover effects of renewable energy production. •Spatial analysis of mechanisms of China's renewable energy production (REP) is required.•The evolution of China's REP presents characteristics of spatial disparity and clustering.•REP shows significant spatial spillover effects affecting neighboring areas.•Transmission infrastructure, environmental regulation, and urbanization level have significant positive effects on REP.